RESULTS OF SURGICAL TREATMENT OF PATIENTS WITH TRAUMATIC INTRACRANIAL HEMATOMAS USING THE MODIFIED CROWN CUTTERS AND PLASTIC OF CIRCULAR AFTER TREPANATION CRANIAL DEFECTS - I. V. Koksharev (Креативная хирургия и онкология, 2017)
The article analyzes  the  results  of surgical treatment of patients with traumatic brain injury using the  modified crown  cutters and  plastic round  after cranial defects. The study aims to improve the results of surgical treatment of patients with TBI. Analyzed the results of surgical treatment of 211 persons, constituting the  main group  (105 operated with the use of modified crown cutters) and control (106, operated by the classical method).Analysis of results showed a decrease in the duration of the first (bone) phase  of craniotomy and a half times in the application of the modified crown cutters.